Spiritual Capital as a Driver of Entrepreneurial Spirit Permanent Community, Gambirsari, Salatiga - Wisnu Sapto Nugroho; J.T. Lobby Loekmono; Suwarto Adi; Agus Supratikno; Spyridon Tsitsigkos (LPPM Universitas PGRI Sumatera Barat, 2023)
This paper proves that spiritual capital is the driving force of entrepreneurial spirit. Spirituality comes from religious values, traditions, and the environment. It can be seen in the community of Tetep, Dukuh Gambirsari Kelurahan Randuacir, Salatiga, Central Java. The entrepreneurial spirit in this community develops due to the impacts of spirituality that manifest in daily practice. The approach of this paper is autoethnography, which is a narrative study based on the experiences of individuals and communities in society. The research utilizes the theories of capital developed by Karl Marx, Weber, and Pierre Bourdieu. Marx emphasized that humans are beings who work, and material possessions serve as the driving force behind work. Weber argues that economic development is closely intertwined with non-economic factors. Bourdieu conceptualizes capital across various dimensions-economic, cultural, social, and symbolic – which are interconnected with habitus and field. The spiritual capital that grows through the practice of life shows that people have the ability to manifest the appreciation of spirituality into the power to survive and thrive amid changing times. In its development, it was also found that some members of the community did not view their businesses solely as a means of survival, but rather as a source of livelihood that created jobs for many people. This spiritual capital is developed in concrete actions through the creations of self-employment in the form of trade and service business. The development of an entrepreneurial society with all its implementations can be used in this approach. Spiritual capital gives rise to fortitude, perseverance, courage to take risks, learners, gratitude, fruitfulness, and honesty. This spirit became the driving force of capitalism for marginalized communities, known as marginal capitalism or village capitalism. They proved the values, culture, and norms of society.